2008
DOI: 10.1007/s00415-008-0753-6
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic cardiovascular function and baroreflex sensitivity in patients with cervical dystonia receiving treatment with botulinum toxin type A

Abstract: Patients with cervical dystonia receiving treatment with botulinum toxin type A have mild, subclinical abnormalities in autonomic cardiovascular regulation and cardiopulmonary baroreflex sensitivity. These changes do not worsen after acute botulinum toxin type A injection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 26 publications
2
10
0
3
Order By: Relevance
“…15,35 Chronic therapy with BoNTA induces subclinical changes in autonomic cardiovascular regulation and cardiopulmonary baroreflex sensitivity. 36 One case of complete atrioventricular block 3 weeks after BoNTA injection has been described, also suggesting an effect on the ANS. 37 A similar effect on the ANS has been described in foodborne botulism.…”
Section: Discussionmentioning
confidence: 98%
“…15,35 Chronic therapy with BoNTA induces subclinical changes in autonomic cardiovascular regulation and cardiopulmonary baroreflex sensitivity. 36 One case of complete atrioventricular block 3 weeks after BoNTA injection has been described, also suggesting an effect on the ANS. 37 A similar effect on the ANS has been described in foodborne botulism.…”
Section: Discussionmentioning
confidence: 98%
“…Another measure of distal effect is evidence of autonomic change after BoNT injection. A short‐term power spectral analysis of heart rate and systolic blood pressure variability, high‐frequency and low‐frequency oscillations of heart rate variability, low frequency/high frequency ratio, and baroreflex sensitivity were measured in 12 patients with cervical dystonia before and 2 to 4 weeks after BoNT‐A injection and were compared with normative data . Their data demonstrated a dose‐dependent effect on neuromuscular transmission in distal muscles, possibly owing to hematogenous spread of the toxin through the bloodstream.…”
Section: Introduction Definitions and Biologic Propertiesmentioning
confidence: 91%
“…Overall, these results suggest that the effect of locally injected, intramuscular BoNT‐A on autonomic cardiovascular innervation cumulates over time. Furthermore, examination of residual urine volumes and of heart rate variability in patients injected with therapeutic doses of BoNT support systemic autonomic dysfunction . None of these findings, however, were noticed by the patient, nor were they clinically relevant.…”
Section: Introduction Definitions and Biologic Propertiesmentioning
confidence: 99%
“…In dystonia patients, most of the autonomic dysfunction is related mainly to treatment with anticholinergic medications or BoNT, and especially with BoNT B, although Tiple et al found that CD patients have mild, subclinical abnormalities in autonomic cardiovascular regulation, heart rate and systolic blood pressure variability, and cardiopulmonary baroreflex sensitivity prior to therapy, which do not worsen after BoNT-A injection [105]. Tinter et al reported patients treated with BoNT-B to have less saliva production and greater severity of constipation, than those treated with BoNT-A [106].…”
Section: Autonomic Dysfunctionmentioning
confidence: 99%